Maintenance of EBPR in an aerobic baffled reactor under varying total phosphorus concentration using dried powdered sludge and molasses. (June 2017) - Yadav, Dharmender; Anand, Raja Sonal; Singh, Rana Pratap; Pruthi, Vikas; Kumar, Pramod
Highlights: Aerobic EBPR is feasible in a baffled reactor using dried powdered sludge and molasses. Aerobic TP release levels correlated with biomass TP content. Aerobic TP uptake occurred even in the presence of carbon source. Release of exo-enzymes by microbes on addition of dried powdered sludge resulted in aerobic EBPR. Abstract: This study examined the performance of EBPR in a baffled reactor operating under fully aerobic conditions using dried powdered sludge and molasses. Total phosphorus (TP) concentration in the used synthetic feed was varied between 1.4–40 mg/L. Experimental results showed that the baffled reactor removed 0.45 ± 0.02–16.9 ± 0.1 mg of TP per g of suspended solids during steady-state operation, and the biomass TP content varied between 1.1 ± 0.02%–22.3 ± 0.1%, suggesting that aerobic EBPR can be achieved using dried powdered sludge and molasses. Biomass TP content correlated with TP release levels. TP uptake took place in the presence of molasses. COD and NH4 + -N removal efficiencies were not affected much by different TP concentrations. TP was primarily stored in the form of intracellular storage of polyphosphate (poly-P). The possible reasons for TP removal were investigated and it was found that the main reason for TP removal in this study was the release of extracellular enzymes by microorganisms due to the addition of dried powdered sludge. Tracer studies results showed that dead space in the reactor ranged from 12.8 to 19.3%. The pattern of flow in the reactor was neither entirely plug flow nor entirely mixed.